The role of sex in sleep deprivation related changes of nociception and conditioned pain modulation - Eichhorn, Nicole; Treede, Rolf-Detlef; Schuh-Hofer, Sigrid (Neuroscience, 2018)
Sex matters both in the clinical field of pain and sleep medicine. Sleep disturbances are highly prevalent in chronic pain patients and have been shown to deteriorate the pain condition. The pathomechanisms by which insomnia aggravates pain are currently unknown. Descending pain control may be compromised by disturbed sleep, but respective studies are few, inconsistent and largely imbalanced with respect to sex. We studied the role of sex on the effect of sleep deprivation on endogenous pain modulation and on nociceptive thresholds in a highly homogenous study population of 18 female (23.8±3.4years) and 18 male (23.3±2.7) healthy students. One night of total sleep deprivation (TSD) was contrasted with one night of habitual sleep in a balanced cross-over design. A cold pressor test was used to explore the effect of TSD on supraspinal pain control. The effect of TSD on nociception was examined by Quantitative Sensory Testing (QST). RM-ANOVA was used for statistical analysis. We found a sex-dependent effect of TSD on descending pain pathways, since the endogenous capacity to inhibit pain was only reduced in sleep deprived females (interaction between ‘sleep condition’ and ‘sex’: p=0.023). While TSD-induced cold and mechanical hyperalgesia were independent of sex, heat pain thresholds did only significantly decrease in sleep deprived females (p=0.041). Our results point to a sex specific impact of TSD on descending pain inhibition. In the future, therapeutic strategies for pain patients with co-morbid insomnia may need to more explicitly respect the specific role of sex.